Sosialisasi Penggunaan Google Classroom dalam Pembelajaran Jarak Jauh secara Asinkron untuk Tutor Bahasa Inggris - Asti Ramadhani Endah Lestari; Elyza Martiarini (Jurnal Abdimas Prakasa Dakara, 2022)
The program is carried out based on the situation that the English Language Course in Depok still conducts the offline meeting due to the tutor's lack of understanding about asynchronous online learning. The aim of this program is to provide socialization of google classroom for the tutors of English Course in Depok. The program focused on training the teacher on how to use google classroom application. Google classroom is one of the products developed by google in order to improve collaboration and create better communication between students and teachers The advantage of google classroom application lies on the flexibility and effectiveness of learning. After finishing the program, it is expected to all participants that they can use google classroom application in their class in order to support the distance learning during pandemic.